1989
DOI: 10.1021/bi00434a057
|View full text |Cite
|
Sign up to set email alerts
|

Nonhuman cells correctly sort and process the human lysosomal enzyme cathepsin D

Abstract: Cathepsin D, like most lysosomal enzymes, undergoes multiple proteolytic cleavages during its lifetime. Although the significance of the earliest cleavages of cathepsin D is apparent (loss of the NH2-terminal signal peptide and activation peptide), functions of the two later cleavages are not understood and do not occur in all species. To examine these later events, a cDNA coding for human cathepsin D, which is normally processed to a two-chain form, was isolated and then expressed in mammalian cells from spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…We have also confirmed the report that the polypeptide pattern of human cathepsin D is similar in human and in transfected heterologous cells [31]. Further, we have shown that the polypeptide backbones of the two subunits of mature cathepsin D obtained by partial deglycosylation are of a very similar size in the two cell types.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have also confirmed the report that the polypeptide pattern of human cathepsin D is similar in human and in transfected heterologous cells [31]. Further, we have shown that the polypeptide backbones of the two subunits of mature cathepsin D obtained by partial deglycosylation are of a very similar size in the two cell types.…”
Section: Discussionsupporting
confidence: 90%
“…Our data extend previous reports on the formation of a partially processed human cathepsin D in Xenopus laevis oocytes micro-injected with human cathepsin D mRNA [30] and of a two-chain human cathepsin D in various heterologous cells transfected with human cathepsin D cDNA [31]. We have shown that the enzyme expressed in BHK cells is enzymically active and that its enzyme activity and antibody reactivity are similar to those of cathepsin D produced in human cells.…”
Section: Discussionsupporting
confidence: 89%
“…5. Sequences of normal cath-D cDNAs were longer in both humans (14,15) and rodents (16,17) compared with cDNAs isolated from estrogen-stimulated breast cancer cell lines (18,19) or from prion-infected cells (scrapie) (20). Moreover, the TATAA sequence was highly conserved at approximately the same position.…”
Section: Resultsmentioning
confidence: 98%
“…In order to facilitate this development, we are working to define the subtle differences in ligand/enzyme interactions that exist between cathepsin D and other aspartic proteinases. Previously, in order to examine active site requirements, human fibroblast procathepsin D has been overexpressed in Escherichia coli (17), refolded from solubilized inclusion bodies (18), and purified using pepstatinyl affinity chromatography (19). The resulting recombinant protein is active, nonglycosylated, not fully processed to the mature amino terminus, and retains 18 residues (27p-44p) of the pro-segment.…”
mentioning
confidence: 99%